Prevajanje izrazov nominalnega naslavljanja glede na spol in družbeni status v filmih Hue and Cry in Indiscreet - Rosič, Eva; Valh Lopert, Alenka (Revija za elementarno izobraževanje, 2018)
Translation of nominal address forms regarding gender, age and social status in the films Hue and Cry and Indiscreet. The article analyses the translation of nominal address forms from English to Slovene. The goal of the research was to determine, with the help of a linguistic analysis of subtitles in the films, the impact of sociolinguistic factors (gender, age and social status were chosen for the purpose of this research) on the translation of nominal address forms. The empirical part is based on a comparison of the original English speech in two films, Hue and Cry and Indiscreet, and their Slovene subtitles.DOI: 10.18690/rei.11.4.293-314.2018COBISS-ID: 24340488